THE EFFECT OF ORLISTAT ADMINISTRATION IN HbA1c, WEIGHT LOSS AND FASTING BLOOD GLUCOSE (FBG) OF OBESITY OR OVERWEIGHT PATIENTS WITH TYPE 2 DIABETES MELLITUS: A META ANALYSIS - Albab, Chabib Fachry; Habibah, Almas Talida; El-Ma’i, Zaha; Hanifullah, Ardan Mulyarajasa; Permatasari, Azmil (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
Orlistat has unique mechanism of action in the pharmacological agents for obesity management in patients with type 2 diabetes mellitus (T2DM). This meta-analysis was to consolidate the existing body of evidence regarding the effect of Orlistat administration on HbA1c levels, weight loss, and fasting blood glucose (FBG) levels in patients who are both obese or overweight and diagnosed with T2DM. The method used in this study was systematic review and meta-analysis which literature search was carried out using PubMed and Science Direct. A systematic review of published studies following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 was conducted. The protocol of this review was registered at PROSPERO. There were 9 selected randomized controlled trials with a total of 1935 patients were included. The analysis found there was significantly reduction in HbA1c (Mean differences [MD]: -0.67; 95% CI: -1.10 - -0.23; p = 0.003), weight loss (Mean differences [MD]: -2.85; 95% CI: -3.23 – -2.48; p < 0.00001), and fasting blood glucose (Mean differences [MD]: -1.23; 95% CI: -1.66 – -0.80; p < 0.00001). The conclusion obtained from the analysis that the effect of orlistat administration demonstrates significant reductions in HbA1c, body weight, and fasting blood glucose levels. It may have a benefical intervention for managing T2DM with obesity or overweight.